PENGARUH ORYZALIN TERHADAP TINGKAT PLOIDI TANAMAN GARUT (Maranta arundinacea L.) - L. Agus Sukamto; Albertus H. Wawo; Fajarudin Ahmad (Buletin Penelitian Tanaman Rempah dan Obat, 2010)
The Effect of Oryzalin on Ploidy Level of Arrowroot Plant (Maranta arundinacea L.)Arrowroot is propagated vegetative so its genetic variation is very narrow. The narrow genetic variation could be broadened through ploidy manipulation. Oryzalin could induce ploidy level of chromosomes and broaden plant genetic variation. Increase in chromosome number usually corresponds with increase stomata, corm, and starch contents. The aims of this research were to broaden germplasms of arrowroot plant by doubling its chromosomes and seeking for individual plants that potentially poly-ploidy to yield increase. This experiment had been done in experimental garden of Cibinong Science Center, February-December 2009. A five-node rhizome was soaked in Oryzalin solution of 0; 10; 20; 30; 40; 50; and 60 µM for 6 days and washed with water. The rhizome was then grown in a polybag containing soil and compost (1:1) in field with 30% shaded net. Oryzalin treatment at high concentration on arrowroot rhizome inhibited plant growth but it increased plant growth at low concentration (10 µM). Several arrowroot plants resulted from Oryzalin treatments were potential polyploid plants. Their stomata were bigger/longer, greener, more rounded, thicker, and more undulated leaves than the control.